TGFβ1, SMAD2, CTNNβ1, and Wnt3a gene mutational status and serum concentrations in individuals with non-small cell lung cancer: TGFβ1, SMAD2, CTNNβ1, and Wnt3a mutational status and serum concentrations - Omer, Hemn Abdalla; Amin, Kawa (Cellular and Molecular Biology, 2023)
The objective of the current investigation was to investigate the diagnostic utility of the serum concentrations and mutational status of TGFβ1, SMAD2, CTNNβ1, and Wnt3a. and the expression levels of human‑related genes in patients with non-small cell lung cancer (NSCLC). The serum concentrations were determined using the ELISA technique, and PCR for genotype variations of TGFβ1, SMAD2, CTNNβ1, and Wnt3a were examined using Sanger sequencing in tissue samples obtained from 93 patients with NSCLC and 84 healthy individuals for blood, and 20 Formalin Fixed Parafﬁn Embedded (FFPE) from normal samples dissected adjacent to the tumour. The findings of the current investigation indicate that individuals diagnosed with NSCLC exhibited significant elevation in the serum levels of CEA and CYFRA21-1, as well as TGFβ1, SMAD2, CTNNβ1, and Wnt3a. In total, 325 mutations in four trialled genes (243 mutations in TGFβ1, 24 mutations in SMAD2,47 mutation Wnt3a and 11 mutations in CTNNβ1) were identified in patients with NSCLC. Furthermore, all mutations were recorded in adenocarcinoma, not squamous and normal adjacent tumour cells. CYFRA21-1 and CEA are more significant between NSCLC and HC, gender, and NSCLC types (p<0.001). In detail, TGFβ1 exhibited the highest rate of mutations among other genes and three types of genomic mutations. Elevated levels and genetic polymorphisms of TGFβ1, SMAD2, CTNNβ1, and Wnt3a may play crucial functions in the pathogenesis and angiogenesis of non-small cell lung cancer (NSCLC). These biomarkers might play a role in future immunologic response and pharmacologically targeted NSCLC therapy.